5. EFEKTIVITAS KERJA SAMA INDONESIA – TIONGKOK DALAM UPAYA PEMBERANTASAN JARINGAN SINDIKAT NARKOBA DI WILAYAH INDONESIA TAHUN 2012-2014 - Bimasakti Aryo Bandung; Hermini Susiatiningsih; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
spread all over the country’s provinces. Those situations were realized by BNN as theprime government organization for Narcotic crime in Indonesia with the main source ofthis problems is China. So that, the Indonesia and Chinese Governments establishedMemorandum of Understanding (MoU) for eradication of illicit drug syndicates in 2012.The purpose of this research is to know the effectiveness of a relation between Indonesiaand China in eradicating illicit drugs syndicates. The research methodologies are withqualitative method, descriptive-analysis type of research, and the data collection ofinterview and literature review type. Since the MoU activated in 2012, a qualitativeanalysis of effectiveness did in purpose of testing the relations between Indonesia andChina based on three parameters, which are: communication intensity, result of eradication,and appreciation. Results from the analysis based on the parameters will prove that thecooperation between the nations are effective and can be refer to ‘Golden Triangle’. Thereason of this results are because there were an increasing number in disclosure of the caseand people arrest that affected to the reduction of the drugs users in 2014.